Therapeutic Endoscopic Ultrasonography: Intratumoral Injection for Pancreatic Adenocarcinoma - Lawrence A. Shirley; Laura K. Aguilar; Estuardo Aguilar-Cordova; Mark Bloomston; Jon P. Walker (Gastroenterology Research and Practice)
Pancreatic adenocarcinoma is an aggressive disease that has poor outcomes despite maximal traditional therapies. Thus, treatment of this cancer demands innovative strategies to be used in addition to standing therapies in order to provide new avenues of care. Here, we describe the technique of using endoscopic ultrasound in order to directly inject both novel and conventional therapies into pancreatic tumors. We detail the rationale behind this strategy and the many benefits it provides. We then describe our technique in detail, including our experience injecting the AdV-tk adenoviral vector to create an in situ vaccine effect.